2011
DOI: 10.1161/strokeaha.110.597914
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Infarction After Subarachnoid Hemorrhage Contributes to Poor Outcome by Vasospasm-Dependent and -Independent Effects

Abstract: Background and Purpose-The pathogenesis of delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage remains incompletely understood. It is generally assumed that it is caused by angiographic vasospasm. Our aim was to clarify the relationship among angiographic vasospasm, neurological worsening, cerebral infarction, and poor outcome and to investigate whether cerebral infarction also contributes to poor outcome by vasospasm-independent effects. Methods-This exploratory analysis used data from 413 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
203
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 287 publications
(219 citation statements)
references
References 24 publications
5
203
0
1
Order By: Relevance
“…This association supports the notion that vasospasm and cerebral ischemia are significant contributors to early and late SAH-related morbidity. 18,22,26,28,29,31,42,43 It also suggests that maneuvers to avoid cerebral ischemia during hospitalization are critical in optimizing the capacity for continued long-term clinical improvement.…”
Section: Figmentioning
confidence: 99%
“…This association supports the notion that vasospasm and cerebral ischemia are significant contributors to early and late SAH-related morbidity. 18,22,26,28,29,31,42,43 It also suggests that maneuvers to avoid cerebral ischemia during hospitalization are critical in optimizing the capacity for continued long-term clinical improvement.…”
Section: Figmentioning
confidence: 99%
“…The sensitivity analysis that reported on functional outcome 3 months after Cerebral infarction and outcome after SAH MDI Vergouwen et al SAH showed similar findings, though the poor outcome analysis had CIs that included 1.00. Previous studies found strong associations between vasospasm, DCI, cerebral infarction, and poor functional outcome (Fisher et al, 1977;Vergouwen et al, 2011;Rabinstein et al, 2004;Fergusen and Macdonald 2007). However, associations do not always represent causal relationships.…”
Section: Discussionmentioning
confidence: 95%
“…Having a direct impact on outcome, the occurrence of cerebral infarction was assessed as a confounding factor [17]. Cerebral infarction was defined as new ischemic lesions, which could not be attributed to surgery or endovascular intervention.…”
Section: Methodsmentioning
confidence: 99%
“…To investigate whether application of NSAIDs had an impact on outcome an unconditional logistic regression, unadjusted and adjusted for confounding covariates, was performed. Age, WFNS grade, occurrence of cerebral infarctions and fever were defined as confounding factors, representing generally accepted, clinically meaningful predictors in patients with SAH [17][18][19][20]. For the significant factors, odds ratios (OR) and their 95% confidence intervals (CI) were calculated.…”
Section: Methodsmentioning
confidence: 99%